2020
DOI: 10.1038/s41598-020-62083-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Semi-Automated Surveillance Algorithm for Cardiac Device Infections: Insights from the VA CART program

Abstract: Procedure-related cardiac electronic implantable device (CIED) infections have high morbidity and mortality, highlighting the urgent need for infection prevention efforts to include electrophysiology procedures. We developed and validated a semi-automated algorithm based on structured electronic health records data to reliably identify CIED infections. A sample of CIED procedures entered into the Veterans’ Health Administration Clinical Assessment Reporting and Tracking program from FY 2008–2015 was reviewed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…This was primarily due to a very high rate of antimicrobial prescriptions, most of which were for infections unrelated to the cardiac device. 26 We found that using a limited set of antimicrobials—those most commonly used to treat Staphylococcal infections—was operationally useful. 40 This finding is congruent with past studies evaluating the utility of a combination of microbiology results and antimicrobial orders for measuring methicillin-resistant S aureus infections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was primarily due to a very high rate of antimicrobial prescriptions, most of which were for infections unrelated to the cardiac device. 26 We found that using a limited set of antimicrobials—those most commonly used to treat Staphylococcal infections—was operationally useful. 40 This finding is congruent with past studies evaluating the utility of a combination of microbiology results and antimicrobial orders for measuring methicillin-resistant S aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“… 32 In our previous work using an algorithm based on structured clinical data from the EMR, PPV ranged from 30% to 40%; however, this study was based on a small sample size. 26 In the present study, we incorporated text mining strategies to discriminate procedure-related infection from other infection diagnoses in a national VA sample, and our algorithm had a PPV of 44% based on our threshold of predicted probability of infection 10% or greater. In practice, this approach was efficient—only 3% of CIED cases met our 10% threshold—and it has the potential to significantly reduce the burden of manual review for infection surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We predict that this intervention would be cost-effective and feasible, given the affordability of disinfectant wipes and their widespread availability within hospitals [ 7 ]. Comparatively, cardiac device implantation infections cost upwards of $50,000 per event [ 9 ]. This study is limited by the imperfect correlation between ATP counts and degree of microbial contamination; however, a strict threshold of cleanliness was employed and very low readings were obtained post-intervention, which is associated with low aerobic colony counts [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%